Taxation of savings vehicles in Brazil and a proposal of a "top-up" income tax - Pedro Humberto Bruno de Carvalho Junior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
The study examines the shift in taxation of open-ended fixed-income funds in Brazil from a realization basis to an accrual basis (locally known as come-cotas), which was introduced in 1998 and more recently extended to include private closed-end funds and offshore trusts through the enactment of Law No. 14,754/2023. The study estimated the effective tax rates of various savings vehicles, including real estate, fixed-income funds and bonds, stocks, pension funds, real estate and agricultural funds, and venture capital funds, among others. It finds that individual investments in rental properties are subject to a higher effective tax rate compared to other investment vehicles, especially financial assets. Finally, the study proposes a 14% "top-up" Individual Income Tax aimed at reducing overall tax regressivity from income tax and social contributions for the top 2% of wealthiest taxpayers. This minimum tax would encompass all sources of income, including dividends, certain unrealized capital gains, and benefits currently exempt by legislation, potentially generating a maximum of R 145.6 billion in revenue.
Keywords: H24; H27; H29; H71; K34; K36; 330; capital gains; individual income tax; wealth concentration; inheritance tax; Brazil